Migration with Pension Reform Expectations - Marek Góra; Anna Ruzik-Sierdzińska (Institute of Labor Economics (IZA), 2018)
Pension reforms, which imply a reduction in the generosity of pension benefits, are becoming widespread in response to the demographic transition. The scale, the timing, and the pace of these reforms vary across countries. In this theoretical article, authors analyse individual migration decisions, by adding a component linked to the expected old-age pension benefits in sending and receiving countries in two cases: when the pension system rules are known, and when there is a risk of the pension systems reforms. The results indicate that when individuals fail to take future pension wealth into account, they can make sub-optimal migration decisions.
Keywords: F22; J24; J26; J61; 330; migration decision; pension benefits; pension reforms; institutional uncertainty